Frequency-Independent Terahertz Anomalous Hall Effect in DyCo5 , Co32 Fe68 , and Gd27 Fe73 Thin Films from DC to 40 THz - Seifert, Tom S (Advanced materials (Deerfield Beach, Fla.), 2021)
© 2021 The Authors. Advanced Materials published by Wiley-VCH GmbH.